PENGEMBANGAN MEDIA PEMBELAJARAN SPARKOL VIDEOSCRIBE BERBASIS BLOG MATERI MENULIS PUISI PADA SISWA KELAS X IPS-A DI MA AL-ANWAR DIWEK JOMBANG - Nurul Ulfa; Fitri Resti Wahyuniarti (STKIP PGRI Jombang, 2019)
This research is motivated by the increasingly rapid technological advances in the world of education and the widespread use of social media among adolescents. In addition, there is no media in the form of blog-based videoscribe that is used to support Indonesian language learning especially poetry writing material. This study aims to explain the process of developing, quality and implementation of blog-based videoscribe media. Research the type of research and development uses Sadiman's model which has seven steps in the development procedure, namely identification of student needs, formulation of instructional goals, formulation of material points, formulation of measuring instruments for success, writing media scripts, validating and revising, conducting trials and revision. Based on the validation process, blog-based video subscription media obtained an overall average yield of 82.6% with very valid qualifications. The results of validation by media experts obtained a value of 72.15% with valid qualifications, while from material experts obtained a value of 88% with very valid qualifications. Indonesian linguists1 scored 80% with valid qualifications, while Indonesian linguists2 scored 84% with highly valid qualifications. The results of validation by IT experts (graphic design) obtained 92% results with very valid qualifications and blogger experts obtained 80% results with valid qualifications. Based on the results of field trials there are significant differences. This was evidenced by the pre-test and post-test values that showed X2 results more than X1 (80.2 ≥ 73.3). So, blog-based video subscription learning media has been proven to significantly improve Indonesian language learning especially for poetry writing material.